Health and labor market impacts of twin birth: Evidence from a Swedish IVF policy - Sonia Bhalotra; Damian Clarke; Hanna Mühlrad; Mårten Palme (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
In vitro fertilization (IVF) has allowed women to delay birth and pursue a career, but it massively increasesthe risk of twin birth. We investigate the extent to which having twins hampers women's careers after birth. To do this, we leverage a single embryo transfer (SET) mandate for IVF procedures implemented in Sweden in 2003, following which the share of twin births showed a precipitous drop of 70%. Linking birth registers to hospitalization and earnings registers, we identify substantial improvements in women's earnings following IVF birth, alongside improvements in maternal and child health and an increase in subsequent fertility. We provide the first comprehensive evaluation of SET. This is relevant given the secular rise in IVF births and the broader rise in the risk of twin birth.
Keywords: J13; I11; I12; I38; J24; 330; twins; IVF; single embryo transfer; career costs of children; gender wage gap; fertility; maternal health; neonatal health; gender